Trichromothrips genus-group (Thysanoptera, Thripidae) from Vietnam, with descriptions of new species in both Okajimaella and Paithrips - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2012)
Okajimaella nonakai sp. n. and Paithrips pornthipae sp. n. are described from bamboo in Vietnam as the third and second spe-cies respectively in these genera. Also newly recorded from bamboo in Vietnam are O. tubercula Nonaka & Janguvitaya and P.circularis Nonaka & Janguvitaya, Neocorynothrips asiaticus Rhamakrishna & Margabandhu, Takethrips megas Nonaka &Jangvitaya, Watanabeotrips yasuakii Okajima, and Yoshinothrips thailandicus Nonaka & Jangvitaya. As a result, nine species from seven genera are now known from bamboo in Vietnam.